2018
DOI: 10.1016/j.jsr.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Occupational interventions for the prevention of back pain: Overview of systematic reviews

Abstract: Exercise interventions with or without educational interventions that can be applied in the workplace have the potential to prevent LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 48 publications
0
37
0
7
Order By: Relevance
“…The authors concluded that multidimensional strategies that involve more than one approach to interventions seem to be most effective and the rationale behind them lies in the multidimensional etiology of LBP. Further evaluations of various workplace interventions are needed [62].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that multidimensional strategies that involve more than one approach to interventions seem to be most effective and the rationale behind them lies in the multidimensional etiology of LBP. Further evaluations of various workplace interventions are needed [62].…”
Section: Discussionmentioning
confidence: 99%
“…Há uma maior prevalência de dor lombar no sexo feminino, e tendendo à maior progressão, quanto maior for a idade 13 . A alta prevalência de dor lombar no sexo feminino pode ocorrer pelo fato das mulheres estarem expostas principalmente à repetitividade, posição viciosa, e trabalho com exigências de grande velocidade em movimentos e repetitivos 6,8,9,14,15 . Várias categorias profissionais já foram apontadas com maiores prevalências para as lombalgias, sendo muitas delas desempenhadas majoritariamente por mulheres, como serviços dos setores domésticos, limpeza, alimentação, informal (diaristas) e têxtil (costureiras) 2 .…”
Section: Discussionunclassified
“…Für die Entwicklung von präventiven Ansätzen bedarf es eines Verständnisses, welche Mechanismen an der Transition von akutem zu chronischem Schmerz beteiligt sind, wie sie identifiziert werden können und welche Interventionen zu welchem Zeitpunkten effektiv und hilfreich sind [24,25]. Unter Umständen geht es dabei weniger um Veränderungen in spezifischen Outcome-Parametern, als vielmehr um die Aufrechterhaltung noch bestehenden Gesundheitsverhaltens.…”
Section: Risikofaktoren Der Schmerzchronifizierungunclassified